A Geological and Geophysical Study of the Geothermal Energy Potential of Pilgrim Springs, Alaska - Turner, Donald L. ed. (Geophysical Institute, University of Alaska, Fairbanks, AK; OSTI, 1980)
The Pilgrim Springs geothermal area, located about 75 km north of Nome, was the subject of an intensive, reconnaissance-level geophysical and geological study during a 90-day period in the summer of 1979. The thermal springs are located in a northeast-oriented, oval area of thawed ground approximately 1.5 kmsup 2 in size, bordered on the north by the Pilgrim River. A second, much smaller, thermal anomaly was discovered about 3 km northeast of the main thawed area. Continuous permafrost in the surrounding region is on the order of 100 m thick. Present surface thermal spring discharge is {approx} 4.2 x 10{sup -3} msup 3 ssup -1 (67 gallons/minute) of alkali-chloride-type water at a temperature of 81 C. The reason for its high salinity is not yet understood because of conflicting evidence for seawater vs. other possible water sources. Preliminary Na-K-Ca geothermometry suggests deep reservoir temperatures approaching 150 C, but interpretation of these results is difficult because of their dependence on an unknown water mixing history. Based on these estimates, and present surface and drill hole water temperatures, Pilgrim Springs would be classified as an intermediate-temperature, liquid-dominated geothermal system; UAG-R-271